2017
DOI: 10.21018/rjcpr.2017.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Age-friendly Advertising: A Qualitative Research on the Romanian Silver Consumers

Abstract: As consumption has become a major aspect that characterizes the life of people currently aged 55 and older, fervent public and academic debates have been raised around the accurate portrayal of seniors in advertising. While most of the previous quantitative and qualitative research highlighted the inappropriate ways of representing elders and the unsuitable framing of advertising claims, little research has been done so far to understand which are seniors' expectations regarding their portrayal in current adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The authors highlighted the value of appropriate theoretical knowledge of elderly needs, the prerequisite of training toward age-friendly architecture and the implication of professionals in the process when medical facilities are parts of the construction [69]. Duduciuc [70] examined advertising models and techniques appropriate for senior consumers (+55 years). The presence of natural surroundings in advertisements empowers all consumers regardless of age.…”
Section: Age-friedly Environments In Romaniamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors highlighted the value of appropriate theoretical knowledge of elderly needs, the prerequisite of training toward age-friendly architecture and the implication of professionals in the process when medical facilities are parts of the construction [69]. Duduciuc [70] examined advertising models and techniques appropriate for senior consumers (+55 years). The presence of natural surroundings in advertisements empowers all consumers regardless of age.…”
Section: Age-friedly Environments In Romaniamentioning
confidence: 99%
“…The presence of natural surroundings in advertisements empowers all consumers regardless of age. The seniors who took part in the study prefer to be shown in the advertisement as active members of society (e.g., surrounded by grandchildren and children, in society, or mentoring young people) [70].…”
Section: Age-friedly Environments In Romaniamentioning
confidence: 99%
“…Esto afecta a las interacciones diarias, incluida la forma en que tratamos a las personas mayores, así como la forma en que nos percibimos a nosotros mismos como "viejos". Una opinión similar es la de los propios ciudadanos mayores, que, por ejemplo, "los mayores prefieren aquellos elencos publicitarios que los retratan como personas activas que desempeñan un papel importante en la vida de sus allegados (es decir, nietos e hijos) y en la sociedad, en general (es decir, que son mentores de los jóvenes en el mercado laboral)" (Duduciuc, 2017). Unas imágenes gerontológicas más positivas de las personas mayores en los medios de comunicación reducirían significativamente el edadismo en cualquier cultura comunicativa.…”
Section: Figura 1 La Distribución De La Imagen Mediática De Las Perso...unclassified